Ética, bioética y bienestar animal: un marco normativo y conceptual - Carmen Liceth García Quintero; Claudia Marcela Duran Chinchilla; Martin Humberto Casadiegos Santana (Mundo Fesc)
The world is changing, and with it, thought and action; at the same time, the scientific and technological advances imposed by the contemporary, globalizing world have generated new ethical paradigms, especially in the way ethics is conceived and to whom it applies. Therefore, it is important to explore animal bioethics, given that it is no secret that animals are often used in experiments, in practical laboratory exercises, on farms, and in homes. They are adopted, yet they are not offered a quality of life appropriate for their well-being. This study will justify the regulations that protect and defend the care and well-being of animals in any space or habitat, especially in those scenarios where animals suffer from abuse. To this end, a documentary review of concepts, regulations, and laws that benefit animals is conducted.